Women, incarceration and HIV: a systematic review of HIV treatment access, continuity of care and health outcomes across incarceration trajectories. (2nd January 2019) - Erickson, Margaret; Shannon, Kate; Sernick, Ariel; Pick, Neora; Ranville, Flo; Martin, Ruth E.; Krüsi, Andrea
Abstract : Objective: The aim of this study was to systematically review the literature on gendered implications of incarceration for HIV outcomes and engagement in care for women living with HIV (WLWH). Design: We systematically searched seven bibliographic databases, for peer-reviewed English-language studies, published between 2007 and 2017 reporting on incarceration, women (transgender inclusive) and HIV. Methods: Articles were included for evaluation if they reported outcomes for at least one of three measures of interest: viral load, antiretroviral therapy (ART) adherence or engagement in care among WLWH along incarceration trajectories. Results: Out of 1119 studies, 24 (2%) met the inclusion criteria. Of these 24 studies, the majority ( n = 23) were conducted in the USA, 19 included samples of women and men and seven studies were transgender inclusive. Our review did not reveal clear sex differences in HIV outcomes during periods of incarceration; however, studies reporting postincarceration outcomes demonstrated significant sex disparities in all three outcomes of interest. Following incarceration, women were less likely to be virally suppressed, less likely to achieve optimal ART adherence and less likely to be engaged in care. Conclusion: Despite growing numbers of incarcerated WLWH globally, there is a substantial gap in research examining the impact of incarceration on HIV outcomes for WLWH. Significant sex disparities in HIV outcomes and engagement in care exist along incarceration trajectories for WLWH, especially postincarceration. For improved health outcomes, research is needed to examine the experiences of WLWH throughout incarceration trajectories to develop interventions tailored to the specific needs of WLWH both during and following incarceration.